Multiple Infections with Viruses of the Family Tymoviridae in Czech Grapevines - Marcela Komínková; Karima Ben Mansour; Petr Komínek; Jana Brožová; Radomíra Střalková (Viruses, 2024)
This study focused on the viruses of the Tymoviridae family that infect grapevines in the Czech Republic. Complete sequences of GFkV (grapevine fleck virus) and GRGV (grapevine red globe virus) from the genus Maculavirus and GRVFV (grapevine rupestris vein feathering virus) and GSyV-1 (grapevine Syrah virus 1) from the genus Marafivirus were obtained using high-throughput sequencing of small RNAs and total RNAs. Mixed infections with these viruses were observed, as well as several variants of these viruses in the same plant. Phylogenetic analysis showed the position of the newly obtained virus isolates within the Tymoviridae family. Recombinant analysis provided evidence of single and multiple intraspecific recombinations in GRGV, GSyV-1, and GRVFV. Additionally, GAMaV, a grapevine virus from the genus Marafivirus, was reported for the first time in the Czech Republic.